Critical analysis of ideological discourse on caste in Shahnameh Based on Michel Foucault’s views (Case study: The story of Anoushirvan and the shoemaker) - Reza Ghanbari Abdolmaleki; Ailin Firoozian Pouresfahani (مطالعات زبانی و بلاغی)
In order to investigate the relationship between ideology and power, the present paper has studied the social discourse of caste in the story of "Anushirvan and the Shoemaker," drawing upon Michel Foucault’s views within the theoretical framework of new historicism. By analyzing the concept of the caste system in this story, the study aims to explore the hidden layers of the text, namely the relationship between ideology and power in Anushirvan’s time. It is also aimed to examine the role of Zoroastrian ideology in promoting and institutionalizing the caste system. To achieve this goal, the present study is organized around two main questions: 1. Is the content of discourse on caste in Anoushirvan’s era a function of the socio-political situation around it? 2. How is Anoushirvan's ideological views on power revealed in the text of Ferdowsi's story? This is an archival study, conducted with a descriptive-analytical approach. The findings of this study shows that the discourse on caste, with the aid of religion as an ideological institution, helps superiors like Anushirvan rule the society and persuades inferiors to accept the status quo. In this way, caste becomes a tool for those in power to generate ideology and suppress their "subjects."